How Does Leverage, Firm Size, and Cash Flow Affect The Financial Distress? In Construction Companies Listed On The Indonesia Stock Exchange In 2018-2022 - Annisa Rosa Meiliana; Muslimin Muslimin; Nindytia Puspitasari Dalimunthe (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The objective of this study is to investigate and gather empirical data about the impact of leverage, firm size, and cash flow on financial distress in construction companies that are listed on the Indonesian Stock Exchange between 2018 and 2022. Research data is evaluated using logistic regression using SPSS 23 for Windows, using secondary data gathered from the company's annual financial reports and official website. According to the study's findings, three factors significantly influence financial distress: 1) leverage has no effect; 2) firm size has a negative effect; and 3) cash flow has no effect. The results of this research can be used as a basis for taking corrective action if there are indications that the company is experiencing financial distress. Thus, to better manage the firm's financial risks, even though company size is the only major element, management should nevertheless keep an eye on other factors like liquidity and cash flow.